Further excavations at Rajim - Sharma, A. K. (B.R, 2019)
Rajim was excavated for three season, first two season's report has benn published. This is the second part of the report which deals with the findings of the third season (2016-17). In the third season we have reached natural soil and structures and antiquities right from the Pre-Mauryan period to Karkhuri period were exposed. It also proved that Rajim was a major port-term along with religious centre. It assumes more importance as it is belived that Shri Ram during his Vangaman passed through Rajim and travelled down to south along the course of Mahanadi and Indravati.